PERLINDUNGAN HAK PENGEMUDI DISABILITAS (TUNA DAKSA) DALAM PERJANJIAN KEMITRAAN ANTARA GO-JEK DAN MITRA KERJA PENGEMUDI DI PEKANBARU - Tedy Desprianda; Emilda Firdaus; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Article 1 paragraph (3) of the Constitution 1945 states that Indonesia is a legal state. Thus the country guarantees the legal rights of its citizens by providing legal protection and legal protection will be the right for every citizen. Legal protections are provided to everyone including disabilities. People know the term disability or disability as someone who bears defects. Society mostly implies people with disabilities as individuals who lose members or body structures such as foot/hand, paralyzed, blind, deaf, etc. Everyone has the potential to become a disability. A person can be a disability not only because of the abnormalities in the womb, but disabilities can also occur in children, adolescents, adults, and older people. Anyone can get an accident on the highway, a work accident, or a victim of natural disasters. This can cause a person to become a disability. In addition, disability protection can also be interpreted as an effort to create an environment and public facilities that are accessibility for the similarity of opportunities for people with disabilities to live independently and in society. That means they also have the right to be independent in working like normal people anyway.Partnerships are efforts involving various sectors, community groups, government agencies and non-Governments to cooperate to achieve a common goal based on their respective principle and role agreements. It means that the essence of the partnership is "mutually beneficial to each party".The type of research used by the authors is a sociological law study that examines the legal aspects by looking at prevailing legislation and comparing with its implementation in the field by surveying. This research is conducted in Pekanbaru City, while the population and samples are the beauty of the parties relating to the investigation, data sources used, primary data, secondary data and tertiary data, data collection techniques in Research with observations, interviews, and library stusion.The result of this study there is still lack of government supervision over the importance of protection against people who are experiencing a disability condition, specifically contained in the partner agreement in the business of Go Jek Pekanbaru. There is still a gap in discrimination as well as lack of awareness from the company about the meaning in the justice in question, as well as the slow responses and resolutions regarding the problem.Keywords: legal protection, disability, partners